Memorial plaques and monuments in Łódź-Śródmieście (the city centre district) commemorating people and events from the history of the city - Kazimierczak, Jarosław (Turyzm/Tourism, 2010)
The aim of this article is a classification of monuments and memorial plaques located in the area of Łódź-Śródmieście (the city centre district) in terms of their tourism value. The author, based on research and analysis, estimates their value as present or potential sites of interest for tourists visiting Łódź and their possible use for tourism aims.